Prospective parental consent for autopsy research following sudden unexpected childhood deaths: a successful model. Issue 5 (12th March 2009) - Thayyil, S; Robertson, N J; Scales, A; Weber, M A; Jacques, T S; Sebire, N J; Taylor, A M
Abstract : Background: Organ retention issues, recent changes in the Coroners' (Amendment) Rules 2005 and the Human Tissue Act have resulted in pessimism regarding prospective consent for paediatric autopsy research in the UK. Objectives: To examine the feasibility and acceptability of a prospective telephone consenting model for post-mortem magnetic resonance (MR) imaging research in HM Coroners' cases. Design: Following each autopsy referral from the HM Coroner, permission to contact the family for research was requested. A family liaison sister, with experience in dealing with bereaved families, then contacted the parents by telephone, explained the study and obtained oral, and then written consent for post-mortem imaging. Setting: London and an area south of London. Results: Of 76 eligible HM Coroners' cases referred during the study period, permission to contact parents (provided by the HM Coroners' Office) was obtained for only 32 cases (42%). The research sister contacted 32 parents during the study period of whom 31 (96.8%) gave oral research consent. "Helping other parents in the future" and "the importance of post-mortem research" were the main reasons for parents wanting to participate in research. Conclusions: Prospective consenting for HM Coroners' cases for research is feasible in children, and can be done ethically by parental consenting via telephone contact before autopsy by appropriately trained staff. However, close co-ordination between mortuary staff, HM Coroners, research staff and medical staff is required. This model may be useful in performing post-mortem research in HM Coroners' cases and in developing paediatric tissue and brain banks in the UK.